Facilitators and inhibitors of attitude and word-of-mouth intention toward adoption of digital municipal service systems: A stimulus-organism-response approach. - Md Shamim Talukder; Quazi Tafsirul Islam; Ziaul Karim (PLoS ONE)
Increased technology adoption has significantly transformed how governments interact with citizens. Today, e-government services and tools are integral to modern public administration. Factors affecting users' adoption of e-government services have been studied in the past. However, this study focuses on citizens' acceptance and resistance to such services, which have not been thoroughly explored. This study addresses the gap by examining the facilitators and inhibitors affecting users' perceptions of the Digital Municipal Service System (DMSS). An integrated research model was developed based on the Stimulus-Organism-Response (SOR) framework. Using Smart-PLS, the study validated 353 respondents' data collected from Bangladesh. The study revealed that platform quality, convenience, social, and inclusiveness values significantly influenced attitudes toward DMSS adoption. On the other hand, tradition and usage barriers significantly negatively impacted attitudes toward DMSS adoption. These findings offer important insights for policymakers involved in developing and implementing e-government services in emerging economies such as Bangladesh. The study also provides a foundation for further research on technology adoption.